The Impacts of Using Google Translate in Writing Thesis for English Education Students at Graduate Program - Fatimah Hidayahni Amin; Demeter Janna Sabatini; Nurdin Noni; Nurharsya Khaer Hanafie; Indrawaty Asfah (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2023)
The objective of this study was to find out the impacts of the use of Google Translate (GT) application to the students’ thesis writing. The samples of the research were chosen purposively, taken the fourth semester students of English Education Department, Graduate Program, at Universitas Negeri Makassar. The study was a descriptive qualitative. It utilized an interview guideline as the primary tool for data collection. The data were analyzed by qualitative analysis employing data condensation, data display, and conclusion and drawing verification. The results of the study showed that the impacts of using GT app to the students’ thesis writing are rewarding in terms of confidence, convenience, time efficiency, and motivation. GT app can increase students’ self-confidence in terms of self-writing skills in composing their thesis. It can also increase the ability to create students’ thesis content. Its use is convenient. Its operation is simple to use at any time, from any location, and in any mobile device. GT app also has an impact on the students’ motivation to complete their thesis quickly, resulting in time efficiency that saves them time in understanding the related literature from GT’s translation as well as the translation of the students’ ideas.Keywords: Google Translate, Thesis Writing, Impacts.